Oral health actions using the ART tecnique: An experience report of the Dental Tutorial Education Program at the State University of Maringa (Research, Society and Development, 2023)
The Tutorial Education Program (PET) of the Dentistry course of the State University of Maringá (UEM), through an extension project, carries out oral health actions of an educational, preventive and curative nature in partnership with the Pastoral da Criança of three municipalities in the region of Maringá-PR. During visits to the communities, educational lectures and curative measures are held to children, through the Atraumatic Restorative Treatment (ART). Thus, the present work aims to disseminate the technique and report the experience of the group with the Atraumatic Restorative Treatment in the extension project: "Insertion of Oral Health Actions with the Child's Pastoral in the municipalities of Mandaguari and Sarandi - State of Paraná''. Taking into account that ART is a technique that requires only manual dental instruments and its approach is minimally invasive, this is the treatment of choice for out-of-office care and with few resources and infrastructure. For this, the members of the group are responsible for the entire organization of the service, as well as the materials used. The tasks are divided according to the level of fitness of each undergraduate. Thus, the project allows children with poor oral health to receive deontological treatment, and it is of paramount importance to use general techniques such as ART to provide better quality of life to the population.